Clinical trial: pilot study of metformin for the treatment of non‐alcoholic steatohepatitis - LOOMBA, R.; LUTCHMAN, G.; KLEINER, D. E.; RICKS, M.; FELD, J. J.; BORG, B. B.; MODI, A.; NAGABHYRU, P.; SUMNER, A. E.; LIANG, T. J.; HOOFNAGLE, J. H. (Alimentary pharmacology & therapeutics, 2009)
Summary Background  Non‐alcoholic steatohepatitis (NASH) is a form of progressive fatty liver disease that is strongly associated with insulin resistance, which suggests that insulin sensitizing agents such as metformin may be beneficial for NASH. Aim  To assess the effects of metformin on insulin sensitivity, body composition, serum alanine aminotransferase (ALT) levels and liver histology in patients with NASH. Methods  Patients underwent liver biopsy, metabolic profiling and imaging studies before and at the end 48 weeks of metformin (2000 mg/day) therapy. The primary endpoint was a three‐point improvement in the histological NASH activity index. Results  Of 28 patients enrolled, 26 (13 females; average age 44 years) completed 48 weeks of treatment and underwent repeat metabolic studies, imaging and liver biopsy. Thirty per cent achieved a histological response. Most patients lost weight, the average being 6 kg. There was a marked association between weight loss and improvements in NASH activity index and ALT levels (both, P < 0.01). Insulin sensitivity also improved, but the degree of change did not correlate with histological improvement. Conclusion  Metformin leads to improvements in liver histology and ALT levels in 30% of patients with NASH, probably by its effects in causing weight loss.